Brand: Evolutionary Cognition, Modern Interpretation and Empirical Research - Grundey, Dainora (Ekonomika, 2002)
The article illustrates one of the major concepts in marketing - brand, with an in-depth analysis of its evolutionary cognition, by presenting some implications of modern interpretation and through the presentation of the results of a customer preference survey of Lithuanian chocolate KARŪNA, carried out in Kaunas, Lithuania. By applying the brand and customer interface concept in contemporary business practice, it is possible to establish communication with potential customers by satisfying their needs. The theoretical generalisations and empirical findings presented in this article could be of interest for marketing theoreticians, general academic society, and persons, directly interested in the development of their brand products.